The effect of ethical orientation, anticipative socialization, and employee organizational commitment to whistleblowing behavior - I Nengah Aristana; Ni Ketut Ayu Ratna Sari (Review of Management, Accounting, and Business Studies, 2023)
The aim of this study was to determine the factors that influence employees' actions in viewing fraud or corporate violations and becoming whistleblowers as part of the internal control system. The goal was to minimize social losses arising from unethical behavior within the company. The population of the study comprised all employees of private hospitals in Bali, specifically in the districts of Jembrana, Tabanan, Badung, Gianyar, and Denpasar. A sample of 100 employees was selected from this population, with data collected through online questionnaires distributed to several employees working in these private hospitals. The data used were primary data collected through online questionnaires (Google Forms). The data analysis technique included a data test instrument consisting of validity and reliability tests. The Classical Assumption Test included the Normality Test, Multicollinearity Test, and Heteroscedasticity Test. Additionally, this study employed Multiple Linear Regression Analysis. Hypothesis testing was conducted using the Hypothesis Test (t-test). The results of this study indicated that there was no significant negative influence of ethical orientation on employee whistleblowing behavior in private hospitals in Bali. However, anticipatory socialization and organizational commitment had significant positive effects on whistleblowing behavior.